Kesalahan Terjemahan dalam Subtitle Film The Help dan Hidden Figures - Meliyanti Sihotang; Shafruddin Tadjuddin; Sri Harini Ekowati (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
The aim of this study was to determine the cultural translation errors in aspect of gender and racial discrimination in movies subtitles The Help and Hidden Figures. This study used a qualitative approach and content analysis method by Krippendorff (2004). This qualitative study was in descriptive qualitative approach. While content analysis use was conversational analysis. Conversation in both movies subtitles were used as data of the study especially the conversation which was the part of gender and racial discrimination. The finding of this study was in form of cultural translation errors in conversation that contained gender and racial discrimination. The result showed, there were four kinds of cultural translation errors in aspect of gender and racial discrimination in movies subtitles The Help and Hidden Figures. They were (1) word choices translation errors; (2) number translation errors; (3) translation errors in cultural material; and (4) translation errors in comprehended SL in the text. All the errors found influeced information and message that delivered to the viewers.